Kemampuan Berpikir Kritis Matematis Dan Pemecahan Masalah Melalui Model Problem Based Learning Berbasis Profil Pelajar Pancasila - Debby Sabrina Hasibuan; Firmansyah Firmansyah; Cut Latifah Zahari (Lembaga Bale Literasi, 2025)
Strengthening 21st-century competencies requires students to possess strong critical thinking skills and the ability to solve problems effectively. One effort to support this is through the implementation of instructional models that are relevant to current educational demands, such as Problem-Based Learning based on the Pancasila Student Profile. This study used a quantitative approach with a quasi-experimental research method with a pretest-posttest control group design. The results showed that students' critical thinking skills in experimental class I, namely students taught using the Pancasila Student Profile-based Problem Based Learning learning model in class X-1 SMA Panca Budi on the material of the Three-Variable Linear Equation System, were in the Very Good category. While in experimental class II, students taught using the Problem Based Learning learning model in class X-2 SMA Panca Budi on the material of the Three Variable Linear Equation System are in the Good category. The mathematical problem solving ability of students in experimental class I, namely students taught using the Problem Based Learning learning model based on the Pancasila Student Profile in class X-1 SMA Panca Budi on the material of the Three Variable Linear Equation System is in the Very Good category. While in experimental class II, students who were taught using the Problem Based Learning learning model in class X-2 SMA Panca Budi on the material of the Three Variable Linear Equation System were in the Bai category. There is a significant difference in the critical thinking and mathematical problem solving skills of students taught using the Problem Based Learning learning model based on the Pancasila Student Profile which is known to be better in improving students' critical thinking and mathematical problem solving skills.